Breeding potential of S4 maize lines in topcrosses for agronomic and forage traits - Marcondes, Mariana Martins; Faria, Marcos Ventura; Mendes, Marcelo Cruz; Gabriel, Andre; Neiverth, Victor; Zocche, Jean Carlos (Acta Scientiarum. Agronomy, 2016)
This study aimed to evaluate the performance of 46 maize lines (S4) obtained from crosses between the commercial hybrids Penta x P30F53 in topcrosses with the commercial simple cross hybrid Dow8460 (tester) and checks (hybrids Penta, P30F53, Dow8460 and Status). The grain yield was evaluated in two environments in Guarapuava, Paraná State, and the effects of genotype, environment and genotype x environment interaction were significant. The grain yield of the topcross hybrids ranged from 8,416 to 13,428 kg ha-1. The agronomic characteristics of the forage and the bromatological characteristics of the silage were evaluated in environment 1. The green mass yield of the forage ranged from 48,767 to 87,714 kg ha-1 and the dry mass yield ranged from 14,749 to 26,130 kg ha-1. The neutral detergent fiber content ranged from 44.85 to 58.45% and the acid detergent fiber content ranged from 28.28 to 37.06%. The relative feed value of the silage ranged between 100.5 and 138.5. The tester, hybrid Dow8460, was efficient to discriminate the relative performance of the S4 lines in the topcrosses.